A novel design of the Roots blower - Tien, Tran Ngoc; Thai, Nguyen Hong (Vietnam Journal of Science and Technology, 2019)
This paper reports a novel curve developed from non - circular gearing theory, which can be applied in rotor profile design of the two - lobe Roots blower. The formulas for calculating the volumetric efficiency and specific flow rate of the blower have also been established. To evaluate this type of the Roots blower, the volumetric efficiency and specific flow rate are being compared with those parameters of the two traditional designs and one recent variant.